2009
DOI: 10.1021/bi901126u
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH on the Rieske Protein from Thermus thermophilus: A Spectroscopic and Structural Analysis,

Abstract: The Rieske protein from Thermus thermophilus (TtRp) and a truncated version of the protein (truncTtRp), produced to achieve a low-pH crystallization condition, have been characterized using UV-visible and circular dichroism spectroscopies. TtRp and truncTtRp undergo a change in the UV-visible spectra with increasing pH. The LMCT band at 458 nm shifts to 436 nm and increases in intensity. The increase at 436 nm versus pH can be fit using the sum of two Henderson-Hasselbalch equations, yielding two pK(a) values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…The ligating histidine that was modified by DEPC, His154, is in bold. and 1.80 (37). The EPR spectrum of DEPC-modified H120Q/ H162Q was consistent with that of a reduced Rieske protein (Figure 6d).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The ligating histidine that was modified by DEPC, His154, is in bold. and 1.80 (37). The EPR spectrum of DEPC-modified H120Q/ H162Q was consistent with that of a reduced Rieske protein (Figure 6d).…”
Section: Resultssupporting
confidence: 73%
“…The purity of each protein was assessed by SDS-PAGE. The concentration of each protein was determined by the difference in AU 572 of the isolated oxidized form and the reduced form obtained by the addition of an excess of sodium dithionite (37). The expression of H120Q/ H162Q (4.3 mg/L of culture) was lower than that of truncTtRp (20 mg/L of culture).…”
Section: Methodsmentioning
confidence: 99%
“…803 Shifts in the UV–vis absorption peaks and CD features upon pH titration are consistent with the two protonation states of the oxidized form. 804 Several studies have shown that multiple inhibitors can bind to the sites close to the cluster and affect the reduction potential of the site. 787,805,806 …”
Section: Fe–s Redox Centers In Electron Transfer Processesmentioning
confidence: 99%
“…However, some local modifications were observed around the cluster. [26] The crucial role of the hydrogen bonds in the immediate cluster environment on the redox potential and on the proton affinity of the two histidines was discussed on the basis of the first X-ray structures [17,27] and it was shown that all sulfur atoms of the cluster participate to the formation of a complex hydrogen-bonded network. The interplay of this network was explored on the basis of site directed mutagenesis studies.…”
mentioning
confidence: 99%